Le clergé et la diffusion du franquisme en Biscaye : un nouveau modèle de prêtre pour un nouveau modèle de société - Severiano Rojo Hernández (Amnis)
This article studies the repression carried out by Franco’s forces in Viscaya against the Basque nationalist clergy. It underlines its dimension and objectives: to neutralize priests susceptible of jeopardizing the establishment of a pro-Franco model of society, and replacing them by clerics whose task was to spread the new ideology.